Milestones in the discovery of antiviral agents: nucleosides and nucleotides - Erik de Clercq (Elsevier, 2012)
In this review article, a number of milestones in the antiviral research field on nucleosides and nucleotides are reviewed in which the author played a significant part, especially in the initial stages of their development. Highlighted are the amino acyl esters of acyclovir, particularly valacyclovir (VACV), brivudin (BVDU) and the valine ester of Cf1743 (FV-100), the 2',3'-dideoxynucleosides (nucleoside reverse transcriptase inhibitors, NRTIs), the acyclic nucleoside phosphonates (S)-HPMPA, (S)-HPMPC (cidofovir) and alkoxyalkyl esters thereof (HDP-, ODE-CDV), adefovir and adefovir dipivoxil, tenofovir and tenofovir disoproxil fumarate (TDF), combinations containing TDF and emtricitabine, i.e., Truvada®, Atripla®, Complera®/Eviplera® and the Quad pill, and the phosphonoamidate derivatives GS-7340, GS-9131, GS-9191 and GS-9219.